2016
DOI: 10.1589/jpts.28.478
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study of knee joint proprioception test results using common test methods

Abstract: [Purpose] To study the correlation of the results obtained from different proprioception test methods, namely, the joint angle reset method, the motion minimum threshold measurement method, and the force sense reproduction method, performed on the same subjects’ knees. [Subjects and Methods] Different proprioception test methods, the joint angle reset method, the motion minimum threshold measurement method and the force sense reproduction method were used to test the knees of 30 healthy young men. [Results] Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Nevertheless, it should be pointed out that, despite slightly worse steadiness, gymnasts had better accuracy in 50% MVC extension task. To summarize, despite intergroup differences in JPS and FS, these results support previous research demonstrating no linear correlation between accuracy of JPS and FS [ 19 , 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, it should be pointed out that, despite slightly worse steadiness, gymnasts had better accuracy in 50% MVC extension task. To summarize, despite intergroup differences in JPS and FS, these results support previous research demonstrating no linear correlation between accuracy of JPS and FS [ 19 , 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…From our current dataset, we can conclude that the effect of angle on shoulder force sense behavior is different from shoulder JPS, where both CE and accuracy improved with increased humeral elevation (King et al, 2013;Suprak et al, 2006). The differing behavior between JPS and force sense may be a contributing factor as to why a correlation has not yet been found between them at any joint (Docherty et al, 2004;Kim et al, 2014;Li et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…This same effect is not reflected at the knee (Iwańska, Karczewska, Madej, & Urbanik, 2015) or the index finger (Walsh, Taylor, & Gandevia, 2011). Another study at the knee (Li et al, 2016) and shoulder (Dover & Powers, 2003) did examine force sense at different joint angles but did not report angle effects. One ankle study did show a greater overshoot as load increased (Dos Santos Haupenthal et al, 2015), but the index finger showed the opposite trend (Walsh et al, 2011).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…5 s]),19 21 22 force perception/load identification (the ability to differentiate between different loads/weights),23 velocity sense (the ability to actively reproduce the velocity of a passive movement),21 active movement extent discrimination (AMEDA, the ability to discriminate between two or more active movements of different ranges of motion)24 or psychophysical threshold methods (the ability to detect and discriminate between different joint positions following passive movements)25 are also reported. However, it appears important to differentiate tests based on the specific targeted sense of proprioception due to the reported lack of correlation between knee position sense, motion sense and force sense 26. Regardless of the targeted proprioceptive sense, there are many factors to be considered when designing a knee joint proprioception test such as determining body position, whether the knee should be weight-bearing or non-weight-bearing, knee angles and speed of movement, occluding visual input, restricting other somatosensory information and minimising extraneous variables.…”
Section: Introductionmentioning
confidence: 99%